Swim bladder mycosis in farmed rainbow trout Oncorhynchus mykiss caused by Phoma herbarum and experimental verification of pathogenicity - Řehulka, J; Kubátová, Alena; Hubka, Vit (Diseases of aquatic organisms, 2020)
In this study, spontaneous swim bladder mycosis was documented in a farmed fingerling rainbow trout from a raceway culture system. At necropsy, the gross lesions included a thickened swim bladder wall, and the posterior portion of the swim bladder was enlarged due to massive hyperplasia of muscle. A microscopic wet mount examination of the swim bladder contents revealed abundant septate hyphae, and histopathological examination showed periodic acid-Schiff-positive mycelia in the lumen and wall of the swim bladder. Histopathological examination of the thickened posterior swim bladder revealed muscle hyperplasia with expansion by inflammatory cells. The causative agent was identified as Phoma herbarum through morphological analysis and DNA sequencing. The disease was reproduced in rainbow trout fingerlings using intraperitoneal injection of a spore suspension. Necropsy in dead and moribund fish revealed extensive congestion and haemorrhages in the serosa of visceral organs and in liver and abdominal serosanguinous fluid. Histopathological examination showed severe hepatic congestion, sinusoidal dilatation, Kupffer cell reactivity, leukostasis and degenerative changes. Fungi were disseminated to the liver, pyloric caeca, kidney, spleen and heart. Although infections caused by Phoma spp. have been repeatedly reported in fish, species identification has been hampered by extensive taxonomic changes. The results of this study confirmed the pathogenicity of P. herbarum in salmonids by using a reliably identified strain during experimental fish infection and provides new knowledge regarding the course of infection.
Keywords: virulence; Histopathology; Fish Diseases; Coelomycetous fungi; Urinary Bladder; Swim bladder; mykózy; zvířata; Oncorhynchus mykiss; Virulence; Experimental infection; močový měchýř; nemoci ryb; Rainbow trout fingerling; Mycoses; Spontaneous infection; Animals